Local Economic Development Strategy through Scenario Planning Approach (Study on the Development of Rural Agro-tourism Areas in Banyuwangi) - Ardhi Kurniawan; Irwan Noor; Endah Setyowati (Wacana Journal of Social and Humanity Studies, 2022)
Local Economic Development (LED) is an appropriate development concept due to the related local or territorial circumstances like considering locality capacity, internal and external factors, and local economic growth so that it has been implemented in many countries. Then the existence of village autonomy and rural area development in Indonesia is such a form of LED implementation. Generally, LED implementation through rural area development has not been successful enough, but in some districts, it has not provided a big impact to improve the people's prosperity. To succeed the LED implementation in developing rural areas, it requires strategies to tackle some problems and challenges and provides a vivid goal in the long term so that the development conducted can synergize each other. Scenario planning is one of the relevant approaches in this case since it accommodates the high complexity and uncertainty. Also, it is used in long-term planning formulation. Moreover, this scenario planning used the TAID method that is tracking, analyzing, imaging, and deciding. Data in this research are compiled by interview, secondary data, and observation to meet the tracking step. Then the output of this will be analyzed using cross-impact to create a scenario in the analyzing step, and the output will be an input for formulating visions and strategies in the imaging and deciding step. This article provides four alternative strategies for developing rural areas which are Dissemination, Optimization, Affirmation, and Reformation.